Mapping study on the fisheries sector in the IOC region - Hanoomanjee, Satish (Technical Centre for Agricultural and Rural Cooperation, 2017)
This study was commissioned by the Technical Centre for Agricultural and Rural Cooperation (CTA) to help guide the Centre’s support to the fisheries sector in the Indian Ocean Commission (IOC) region in the context of CTA’s East Africa Regional Business Plan and its work on value chains. The study provides an overview of the fish value chains in four countries – Comoros, Madagascar, Mauritius/Rodrigues and Seychelles – together with recommendations for future action. Key actors and institutions, value-chain development initiatives, policies and regulatory frameworks are presented and analysed.